2018
DOI: 10.1155/2018/3890637
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Miscibility of Polypyrrole and Polyaniline Polymer Blends

Abstract: We report on the miscibility and phase behaviour of polypyrrole-polyaniline (PPy/PANI) as a function of blend composition. The PPy/PANI blends were prepared by solution processing method, using dimethyl sulfoxide (DMSO) solvent. Characterization of the polymer blends was carried out based on the data analysis from Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The PPy/PANI system was successfully formed blends in DMSO solvent. The polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…45 The other two peaks at 32.7°and 36.3°indicate chain ordering in PPy macromolecules. 44 The three intense peaks at 16.1°, 21.6°, and 32.6°i n the presence of 2,6-pyridinedicarboxylic acid showed that XRD pattern recorded for phase composition. It can also be proved from the observation of different X-ray diffraction peaks between PPy and DCA in the structure that phase separation.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…45 The other two peaks at 32.7°and 36.3°indicate chain ordering in PPy macromolecules. 44 The three intense peaks at 16.1°, 21.6°, and 32.6°i n the presence of 2,6-pyridinedicarboxylic acid showed that XRD pattern recorded for phase composition. It can also be proved from the observation of different X-ray diffraction peaks between PPy and DCA in the structure that phase separation.…”
Section: Resultsmentioning
confidence: 94%
“…1b, pure PPy was exhibited a fringed micelles model of nanostructured polymers with low degree of crystallinity. 44 The sharp patterns at 16.2°, 18.2°, and 21.8°may be assigned to the spacing the ring planes in the PPy chains. 45 The other two peaks at 32.7°and 36.3°indicate chain ordering in PPy macromolecules.…”
Section: Resultsmentioning
confidence: 99%